Synthetic Receptors Induce Anti Angiogenic and Stress Signaling on Human First Trimester Cytotrophoblast Cells - Pantho, Ahmed F. (Int J Environ Res Public Health, 2017)
The cytotrophoblast (CTB) cells of the human placenta have membrane receptors that bind certain cardiotonic steroids (CTS) found in blood plasma. One of these, marinobufagenin, is a key factor in the etiology of preeclampsia. Herein, we used synthetic receptors (SR) to study their effectiveness on the angiogenic profile of human first trimester CTB cells. The humanextravillous CTB cells (Sw.71) used in this study were derived from first trimester chorionic villus tissue. Culture media of CTB cells treated with ≥1 nM SR level revealed sFlt-1 (Soluble fms-like tyrosine kinase-1) was significantly increased while VEGF (vascular endothelial growth factor) was significantly decreased in the culture media (* p < 0.05 for each) The AT(2) receptor (Angiotensin II receptor type 2) expression was significantly upregulated in ≥1 nM SR-treated CTB cells as compared to basal; however, the AT(1) (Angiotensin II receptor, type 1) and VEGFR-1 (vascular endothelial growth factor receptor 1) receptor expression was significantly downregulated (* p < 0.05 for each). Our results show that the anti-proliferative and anti-angiogenic effects of SR on CTB cells are similar to the effects of CTS. The observed anti angiogenic activity of SR on CTB cells demonstrates that the functionalized-urea/thiourea molecules may be useful as potent inhibitors to prevent CTS-induced impairment of CTB cells.